Composite diaphragm, preparation method thereof and secondary battery

By using composite separators in lithium metal batteries, the problems of lithium dendrites and thermal runaway are solved, and the battery's high cycle stability and safety are achieved.

CN119481586APending Publication Date: 2025-02-18JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411687035.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Lithium metal negative electrode materials produce lithium dendrites during circulation, resulting in a decrease in electrochemical and safety performance, and the rapid charging and discharge process may cause thermal runaway and safety accidents.

Method used

Using a composite separator, the separator consists of a mullite fiber layer and a composite layer containing one-dimensional carbon material and polydopamine. By adjusting the layer thickness ratio and material, it inhibits the growth of lithium dendrites, protects the SEI film, and prevents the battery cell. The diaphragm shrinks when thermal runaway.

Benefits of technology

Effectively inhibit the growth of lithium dendrites, protect the SEI film, improve the cycle stability and safety of the battery, extend the battery life, and reduce the risk of thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481586A_ABST
    Figure CN119481586A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm, a preparation method thereof and a secondary battery. The composite diaphragm comprises a first layer and a second layer, the first layer is a mullite fiber layer, the second layer comprises a mixture, the mixture comprises a polymer and a compound, and the compound comprises a one-dimensional carbon material and polydopamine coating the surface of the one-dimensional carbon material. The composite diaphragm disclosed by the invention not only can restrain the problem of lithium dendrites, but also can protect an SEI (Solid Electrolyte Interphase) membrane, can also prevent the diaphragm from being reduced when a battery cell is in thermal runaway, and can also reduce the electrolyte infiltration time of the diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a composite diaphragm and a preparation method thereof and a secondary battery. Background Art

[0002] Lithium metal has high theoretical specific capacity, low density and low chemical potential. As a negative electrode material, it can perfectly meet the needs of high energy density and is expected to develop further in the fields of new energy vehicles, mobile electronics, wearable electronic products, etc. However, the uncontrollable lithium dendrites produced during the deposition and stripping of metal lithium will greatly reduce the electrochemical performance and safety performance of the battery. This is the key reason why lithium metal negative electrode materials have not yet been commercialized on a large scale, and it is also a safety problem that needs to be solved urgently in the industry. In addition, the repeated stripping and deposition behavior of lithium metal electrodes during cycling will inevitably produce volume expansion, resulting in repeated destruction and reconstruction of the SEI film on the surface solid electrolyte interface. At the same time, the metal lithium that melts from the root is easy to detach from the conductive system and form "dead lithium" that is difficult to reuse. These will affect the Coulomb efficiency of the battery cycle and greatly shorten the battery life. More seriously, the unlimited growth of dendritic lithium dendrites will have the risk of piercing the diaphragm. Once this happens, the positive electrode will be directly short-circuited, causing a sharp increase in local temperature, thereby causing thermal runaway, and then leading to major safety accidents such as combustion or even explosion.

[0003] Moreover, the rapid charge and discharge process will produce local heat accumulation, and the local high temperature will accelerate the Li + The local reaction rate leads to the formation of lithium dendrites.

[0004] In response to the above problems, scientific researchers have conducted a lot of research and made significant progress, which can be roughly summarized as follows:

[0005] (1) Constructing a three-dimensional conductive skeleton as a host material for lithium metal can significantly improve the volume expansion problem during the circulation of lithium metal. At the same time, the conductive skeleton can reduce the generation of "dead lithium" and thus improve the utilization rate of lithium metal;

[0006] (2) The preparation of high-performance functionalized separators can also effectively inhibit the growth of lithium dendrites. Among them, constructing separators with high ionic conductivity and high surface Young's modulus has been proven to be an effective measure to inhibit lithium metal dendrites.

[0007] (3) Studying the heat transfer performance of the diaphragm is also important for inhibiting lithium dendrites, because it is closely related to the formation of lithium dendrites. Optimizing the diaphragm material for safety issues can improve the cycling stability of lithium metal, but it cannot prevent the heat rise and heat diffusion during thermal runaway of the battery cell. During thermal runaway and temperature rise, the diaphragm structure is easily reduced, leading to battery cell failure.

[0008] Therefore, providing a diaphragm that can both suppress the problem of lithium dendrites and protect the SEI film and prevent the diaphragm from shrinking during thermal runaway of the battery cell is a technical problem that needs to be solved urgently. Summary of the invention

[0009] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a composite diaphragm and a preparation method thereof and a secondary battery.

[0010] To achieve the above object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a composite membrane, comprising a first layer and a second layer, wherein the first layer is a mullite fiber layer, and the second layer comprises a mixture, wherein the mixture comprises a polymer and a composite, and the composite comprises a one-dimensional carbon material and polydopamine coated on the surface of the one-dimensional carbon material.

[0012] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0013] Preferably, the thickness of the first layer is A, the thickness of the second layer is B, and A and B satisfy the relationship:

[0014] 1 / 8≤A / (A+B)≤5 / 8.

[0015] Illustratively, A / (A+B) may be, for example, 1 / 8, 2 / 8, 3 / 8, 4 / 8 or 5 / 8, etc.

[0016] In the present invention, A / (A+B) refers to the ratio of the thickness of the first layer to the total thickness of the first layer and the second layer, wherein the first layer is a mullite fiber layer serving as a heat insulating layer.

[0017] Preferably, the mullite fiber layer is a porous layer formed by overlapping mullite fibers. The mullite fiber layer of the present invention is composed of only mullite fibers and does not contain other substances.

[0018] Preferably, the polymer is a fluorine-containing polymer, preferably including at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), tetrafluoroethylene-perfluoroalkyl vinyl ether (PFA), polyvinylidene fluoride (PVDF), fluorinated polyimide (FPI), fluororubber (FKM), fluorovinyl ether copolymer (FEVE), perfluoropolyether (PFPE), perfluoroethylene propylene copolymer (FEP) and fluorinated polyarylether nitrile (FPEN).

[0019] Preferably, in the composite, the one-dimensional carbon material includes at least one of carbon nanotubes and carbon fibers.

[0020] Preferably, in the composite, the mass ratio of the one-dimensional carbon material to the polydopamine is 0.01-0.1.

[0021] Preferably, the mass ratio of the composite to the polymer is 0.005-0.1.

[0022] Preferably, the first layer and the second layer are both located at the outermost sides of the composite diaphragm.

[0023] In a second aspect, the present invention provides a method for preparing the composite diaphragm as described in the first aspect, comprising the following steps:

[0024] (1) preparing a mullite fiber layer;

[0025] (2) dispersing the one-dimensional carbon material, dopamine hydrochloride and a stabilizer in a first solvent and reacting them to obtain a composite;

[0026] (3) dissolving the polymer and the composite in a second solvent and stirring them uniformly to obtain a composite solution;

[0027] (4) coating the composite solution on the mullite fiber layer prepared in step (1), and drying the composite membrane.

[0028] In one embodiment of the present invention, by adding a stabilizer in step (2), it can be ensured that the surface of the one-dimensional carbon material core is covered with a dopamine shell layer to form a stable core-shell structure.

[0029] As a preferred technical solution of the preparation method of the present invention, step (1) comprises: providing a dispersion medium, adding mullite fibers into the dispersion medium to form a dispersion system, and drying the dispersion system and then high-temperature molding to obtain the mullite fiber layer.

[0030] Preferably, after adding mullite fibers into the dispersion medium, heating and stirring steps are performed to form the dispersion system, and the heating temperature is 80°C-120°C.

[0031] Preferably, the viscosity of the dispersed system is μ 2 , 50cP≤μ 2 ≤30000cP.

[0032] Preferably, the drying step is performed after the dispersed system is allowed to stand and filtered.

[0033] Preferably, the sintering temperature of the high temperature forming is 800°C-1800°C.

[0034] Preferably, the sintering time of the high temperature forming is 0.5h-10h.

[0035] Preferably, in the high temperature forming step, the dried precursor is sandwiched between sintering plates for sintering.

[0036] Preferably, the dispersion medium is a glue solution, and the glue solution is obtained by mixing a binder and water and heating them.

[0037] Preferably, the temperature at which the binder and the water are mixed and heated is 80°C-120°C.

[0038] Preferably, the viscosity of the glue solution is μ 1 , 50cP≤μ 1 ≤20000cP.

[0039] Preferably, the binder includes at least one of polyacrylamide, silica sol and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0040] Preferably, the mass ratio of the mullite fiber to the binder is 10-100.

[0041] As a preferred technical solution of the preparation method of the present invention, the first solvent in step (2) is an aqueous solvent, wherein the aqueous solvent refers to a solvent containing water.

[0042] Preferably, the aqueous solvent comprises ethanol and water.

[0043] Preferably, the stabilizer includes at least one of 3-(methacryloxypropyl)tris(trimethylsiloxy)silane aqueous solution, anhydrous ethanol and nitrogen methyl pyrrolidone.

[0044] Preferably, step (2) comprises:

[0045] (a) dispersing the one-dimensional carbon material in the first solvent to obtain a first solution;

[0046] (b) adding the dopamine hydrochloride and the stabilizer to the first solution, heating and stirring to obtain a composite.

[0047] This method generates adhesive PDA through the self-polymerization of dopamine hydrochloride, which adheres to the surface of a one-dimensional carbon material to form an inorganic-organic composite with a core-shell structure.

[0048] In one embodiment, the uniform stirring in step (3) is performed by heating at 45°C-65°C and stirring for 20min-40min.

[0049] In a third aspect, the present invention provides a secondary battery comprising a positive electrode, a negative electrode and a separator, wherein the separator is a composite separator as described in the first aspect or a composite separator prepared by the method described in the second aspect, wherein the first layer of the composite separator is arranged close to the negative electrode, and the second layer is arranged close to the positive electrode.

[0050] Preferably, the negative electrode is a lithium metal negative electrode.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) The composite diaphragm of the present invention has a high porosity and good affinity for the electrolyte, which can reduce the electrolyte infiltration time of the diaphragm; it can also suppress the problem of lithium dendrites, protect the SEI membrane, and prevent the diaphragm from shrinking during thermal runaway of the battery cell. Its porosity is above 41.7%, its contact angle with the electrolyte is below 11.2°, and its area shrinkage at 200°C is below 11.2%.

[0053] (2) The preparation method of the composite diaphragm of the present invention is simple, easy to operate, and suitable for industrial production.

[0054] (3) The battery manufactured using the composite diaphragm of the present invention has high first efficiency and cycle performance, with the first efficiency being above 85.3% and the 2000 cycle capacity retention rate being above 82.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 These are SEM images of the mullite fiber diaphragm, the second layer in the composite diaphragm, and the first layer in the composite diaphragm, where (a) corresponds to the mullite fiber, (b) corresponds to the second layer, and (c) corresponds to the first layer.

[0056] Figure 2 These are SEM images of the negative electrode surfaces of batteries made of the diaphragms of Example 1 and Comparative Example 1 after 500 cycles, wherein (a) corresponds to Comparative Example 1, and (b) corresponds to Example 1. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0058] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0059] In one embodiment, the present invention provides a composite membrane, which includes a first layer and a second layer, wherein the first layer is a mullite fiber layer, and the second layer includes a mixture, wherein the mixture includes a polymer and a composite, and the composite includes a one-dimensional carbon material and polydopamine coated on the surface of the one-dimensional carbon material.

[0060] The composite diaphragm provided in one embodiment of the present invention can not only suppress the problem of lithium dendrites, but also protect the SEI film, and can also prevent the shrinkage of the diaphragm during thermal runaway of the battery cell, delay the occurrence time of runaway and reduce the peak temperature. The technical principle is:

[0061] First, mullite fiber (3Al 2 O 3 ·2SiO 2 ) is a common aluminum silicate fiber, which is mainly composed of polycrystalline particles, has good chemical inertness, low thermal conductivity and very high melting temperature, so the mullite fiber layer can suppress the problem of lithium dendrites and improve the safety of lithium metal batteries. Moreover, compared with mullite, one-dimensional carbon materials have a considerable thermal conductivity (for example, the thermal conductivity of carbon nanotubes is ~3000W / m·K), which can completely disperse and evenly distribute the heat of the second layer. Therefore, the mullite fiber layer isolates the heat diffusion from the electrode (such as the negative electrode), and the one-dimensional carbon material evenly distributes the transferred heat, further solving the problem of lithium dendrites caused by heat accumulation.

[0062] Second, mullite fiber has excellent mechanical strength. Therefore, the mullite fiber layer in the composite diaphragm can prevent the shrinkage and puncture risk of the diaphragm during thermal runaway of the battery cell.

[0063] Third, the important component of mullite is Al 2 O 3 and SiO 2 , both of which are excellent lithium-philic substances. Due to their excellent lithium-philic properties, Li + Deposition along the surface of mullite fibers promotes Li + The uniform deposition of the nanostructured carbon nanotubes effectively reduces the growth of dendrites that may pierce the separator and enhances the cycle stability of the battery cell.

[0064] Furthermore, the composite diaphragm can also reduce the electrolyte infiltration time of the diaphragm. This is because: polydopamine (PDA) coats the one-dimensional carbon material to form an organic-inorganic composite with a core-shell structure, which avoids the risk of short circuit caused by the conductivity of the one-dimensional carbon material, and can also utilize the hydrophilic surface properties of PDA, which is beneficial to the infiltration of the electrolyte. At the same time, mullite also has low surface energy, which is conducive to rapid infiltration. Therefore, the synergistic effect of the two can greatly increase the liquid absorption characteristics of the material and reduce the electrolyte infiltration time during high-temperature infiltration of the battery cell.

[0065] In one embodiment, the thickness of the first layer is A, the thickness of the second layer is B, and A and B satisfy the relationship:

[0066] 1 / 8≤A / (A+B)≤5 / 8.

[0067] Illustratively, A / (A+B) may be, for example, 1 / 8, 2 / 8, 3 / 8, 4 / 8 or 5 / 8, etc.

[0068] In the present invention, A / (A+B) refers to the ratio of the thickness of the first layer to the total thickness of the first layer and the second layer, wherein the first layer is a mullite fiber layer, which serves as an insulating layer. If the ratio of the thickness of the first layer is too small, the thermal insulation performance will be reduced; the second layer serves as a supporting layer. If the ratio of the thickness of the first layer is too large, the ratio of the thickness of the second layer is too small, which will cause the composite diaphragm to have a reduced ability to resist shrinkage when subjected to high temperatures.

[0069] In one embodiment, the mullite fiber layer is a porous layer formed by overlapping mullite fibers. The composition of the mullite fiber layer of the present invention is only mullite fibers, and does not contain other substances. The advantage of such a configuration is that the introduction of the mullite fiber layer without other substances can more fully reduce the contact angle of the diaphragm and accelerate the electrolyte infiltration.

[0070] In one embodiment, the polymer is a fluorine-containing polymer, preferably including polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), tetrafluoroethylene-perfluoroalkyl vinyl ether (PFA), polyvinylidene fluoride (PVDF), fluorinated polyimide (FPI), fluororubber (FKM), fluorovinyl ether copolymer (FEVE), perfluoropolyether (PFPE), perfluoroethylene propylene copolymer (FEP) and fluorinated polyarylether nitrile (FPEN) At least one. Due to the fluorine-containing polymer, the high-density strong electron-withdrawing fluoride functional group can avoid the formation of a space charge layer and protect the SEI film. At the same time, the electrophilic properties of mullite synergize with the strong electron-withdrawing fluoride functional group, so that the SEI film can be protected while promoting the uniform deposition of lithium ions, solving the side reaction to avoid the rupture and rebirth of the SEI film, and effectively reducing the accumulation of dead lithium on the surface of the lithium metal negative electrode to maintain the lithium ion diffusion flux during the cycle.

[0071] In one embodiment, in the composite, the one-dimensional carbon material includes at least one of carbon nanotubes and carbon fibers.

[0072] In one embodiment, in the composite, the mass ratio of the one-dimensional carbon material to the polydopamine is 0.01-0.1, for example, it can be 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09 or 0.1, etc.

[0073] In one embodiment, the mass ratio of the complex to the polymer is 0.005-0.1, for example, it can be 0.005, 0.008, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09 or 0.1, etc.

[0074] In one embodiment, the first layer and the second layer are both located on the outermost side of the composite diaphragm. The advantage of such a configuration is that the outermost layer has high mechanical strength and thermal insulation performance, which can ensure the mechanical toughness of the diaphragm and inhibit thermal runaway.

[0075] In another embodiment, the present invention provides a method for preparing the composite diaphragm as described above, comprising the following steps:

[0076] (1) preparing a mullite fiber layer;

[0077] (2) dispersing the one-dimensional carbon material, dopamine hydrochloride and a stabilizer in a first solvent and reacting them to obtain a composite;

[0078] (3) dissolving the polymer and the composite in a second solvent and stirring them uniformly to obtain a composite solution;

[0079] (4) coating the composite solution on the mullite fiber layer prepared in step (1), and drying the composite membrane.

[0080] The preparation method of the composite diaphragm provided in one embodiment of the present invention is simple, easy to operate, and suitable for industrial production.

[0081] As a preferred technical solution of the preparation method of the present invention, step (1) comprises: providing a dispersion medium, adding mullite fibers into the dispersion medium to form a dispersion system, and drying the dispersion system and then high-temperature molding to obtain the mullite fiber layer.

[0082] In one embodiment, after adding mullite fiber to the dispersion medium, heating and stirring steps are performed to form the dispersion system, and the heating temperature is 80°C-120°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, etc.

[0083] In one embodiment, the viscosity of the dispersed system is μ 2 , 50cP≤μ 2 ≤30000cP, illustratively, μ 2It can be 50cP, 100cP, 200cP, 300cP, 500cP, 700cP, 800cP, 1000cP, 1200cP, 1400cP, 1800cP, 2000cP, 2500cP, 3000cP, 3500cP, 4000cP, 4500cP, 5000cP, 5500cP, 6000cP, 6500cP, 7000cP, 7500cP, 8000cP, 8500cP, 9000cP 0cP, 10000cP, 11000cP, 12000cP, 13000cP, 14000cP, 15000cP, 16000cP, 17000cP, 18000cP, 19000cP, 20000cP, 21000cP, 22000cP, 23000cP, 24000cP, 25000cP, 26000cP, 27000cP, 28000cP, 29000cP or 30000cP, etc.

[0084] In one embodiment, the drying step is performed after the dispersed system is allowed to stand and filtered.

[0085] In one embodiment, the sintering temperature of the high temperature forming is 800℃-1800℃, for example, it can be 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, 1500℃, 1550℃, 1600℃, 1650℃, 1700℃, 1750℃ or 1800℃, etc.

[0086] In one embodiment, the sintering time of the high temperature forming is 0.5h-10h, for example, it can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h or 10h, etc.

[0087] In one embodiment, in the high temperature forming step, the dried precursor is sandwiched between sintering plates for sintering.

[0088] In one embodiment, the dispersion medium is a glue solution obtained by mixing and heating a binder and water. Since the dispersion medium will subsequently undergo a high-temperature molding step during the preparation of the mullite fiber layer, during which the binder will be removed, the prepared mullite fiber layer does not contain a binder.

[0089] In one embodiment, the temperature at which the binder and the water are mixed and heated is 80°C-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C.

[0090] In one embodiment, the viscosity of the glue solution is μ 1 , 50cP≤μ 1 ≤20000cP, illustratively, μ 1 It can be 50cP, 100cP, 200cP, 300cP, 500cP, 700cP, 800cP, 1000cP, 1200cP, 1400cP, 1800cP, 2000cP, 2500cP, 3000cP, 3500cP, 4000cP, 4500cP, 5000cP, 5500cP, 6000cP P, 6500cP, 7000cP, 7500cP, 8000cP, 8500cP, 9000cP, 10000cP, 11000cP, 12000c P, 13000cP, 14000cP, 15000cP, 16000cP, 17000cP, 18000cP, 19000cP or 20000cP, etc.

[0091] In one embodiment, the binder includes at least one of polyacrylamide, silica sol and polyvinylidene fluoride-hexafluoropropylene copolymer.

[0092] Preferably, the mass ratio of the mullite fiber to the binder is 10-100, for example, it can be 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100, etc.

[0093] As a preferred technical solution of the preparation method of the present invention, the first solvent in step (2) is an aqueous solvent, wherein the aqueous solvent refers to a solvent containing water.

[0094] In one embodiment, the aqueous solvent comprises ethanol and water.

[0095] In one embodiment, the stabilizer includes at least one of an aqueous solution of 3-(methacryloxypropyl)tris(trimethylsiloxy)silane, anhydrous ethanol, and nitrogen methyl pyrrolidone.

[0096] In one embodiment, step (2) comprises:

[0097] (a) dispersing the one-dimensional carbon material in the first solvent to obtain a first solution;

[0098] (b) adding the dopamine hydrochloride and the stabilizer to the first solution, heating and stirring to obtain a composite.

[0099] This method generates adhesive PDA through the self-polymerization of dopamine hydrochloride, which adheres to the surface of a one-dimensional carbon material to form an inorganic-organic composite with a core-shell structure.

[0100] In one embodiment, the uniform stirring in step (3) is as follows: heating and stirring at 45°C-65°C (for example, 45°C, 47°C, 50°C, 52°C, 55°C, 58°C, 60°C, 63°C or 65°C, etc.) for 20min-40min (for example, 20min, 23min, 25min, 30min, 35min or 40min, etc.).

[0101] In another embodiment, the present invention provides a secondary battery, including a positive electrode, a negative electrode and a separator, wherein the separator adopts the above-mentioned composite separator or a composite separator prepared by the above-mentioned method, and in the composite separator, the first layer is arranged close to the negative electrode, and the second layer is arranged close to the positive electrode.

[0102] In one embodiment, the negative electrode is a lithium metal negative electrode. On the one hand, the lithium metal negative electrode has the advantage of high energy density; on the other hand, since the above-mentioned composite separator is used and the first layer is arranged close to the negative electrode, the problem of lithium dendrites can be effectively suppressed and the shrinkage of the separator can be prevented when the battery cell overheats and runs away.

[0103] The battery assembled using the composite diaphragm of the present invention has a higher first efficiency and excellent cycle performance.

[0104] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0105] The following are typical but non-limiting examples:

[0106] The short mullite fiber used in the embodiment of the present invention is purchased from Aok Refractory Materials Co., Ltd., and the model is AK-65.

[0107] Example 1

[0108] The present embodiment provides a composite diaphragm, the composite diaphragm is composed of a stacked first layer and a second layer, the first layer is a mullite fiber layer, the mullite fiber layer is a porous layer formed by overlapping mullite fibers, the second layer includes a mixture, the mixture includes a polymer (polyvinylidene fluoride-hexafluoropropylene copolymer, PVDF-HFP) and a composite, the composite includes a one-dimensional carbon material (carbon nanotubes, CNTs) and polydopamine coated on the surface of the one-dimensional carbon material, the mass ratio of the composite to the polymer is 0.05, and the mass ratio of the one-dimensional carbon material to the polydopamine in the composite is 0.05;

[0109] The thickness of the first layer is A, the thickness of the second layer is B, A=3 μm, B=3 μm, and A / (A+B) is 1 / 2.

[0110] This embodiment also provides a method for preparing the above-mentioned composite diaphragm, comprising the following steps:

[0111] 1. Preparation of Mullite Fiber Diaphragm

[0112] First, disperse 2.5g polyacrylamide and 10g silica sol in 25mL pure water and stir mechanically for 2h until the solution is uniform. Then add 5.0g short mullite fiber to the solution and continue stirring until a uniform slurry is formed. After stirring evenly, pour the slurry into a homemade mold, let it stand for 1h, filter out the excess solution, and then put the mold into a 60℃ oven to dry for 10h. After drying, cut the blank with a punching die, and finally sandwich the cut blank between magnesium oxide support plates and place it in a tubular furnace and sinter at 1300℃ for 2h to obtain a mullite fiber diaphragm. See its SEM image. Figure 1 (a) in .

[0113] 2. Preparation of CNT@PDA core-shell nanotubes

[0114] Multi-walled carbon nanotubes (CNTs) were added to water and ethanol in a mass ratio of 1:1, and ultrasonically dispersed for 1 hour to obtain a CNTs dispersion. Dopamine hydrochloride (DA) was then added to the CNTs dispersion and magnetically stirred for 5 minutes, and then a methacryloxypropyl trimethoxysilane aqueous solution (Tris aqueous solution) was added and stirred for 12 hours. Among them, the mass ratio of CNTs, DA and Tris was 1:2:1.5, and then centrifuged, washed with deionized water 3 times, and placed in an 80°C oven to dry for 24 hours to obtain CNT@PDA core-shell nanotube powder.

[0115] 3. Preparation of CNT@PDA / mullite composite membrane

[0116] At room temperature, PVDF-HFP powder and CNT@PDA core-shell nanotubes were dissolved in acetone and rapidly magnetically stirred until the particles were completely dispersed and uniformly dispersed, and then placed in a 55°C water bath, stirred for 30 min, and then cooled and stirred at room temperature to obtain a composite solution;

[0117] The coating was carried out using a coating machine at 1 cm s -1 The composite solution was coated on the mullite fiber membrane at a coating speed of 1000 nm and dried at room temperature for 1 h to obtain a CNT@PDA / mullite composite membrane, i.e., a composite membrane. The SEM image of the second layer of the composite membrane is shown in Figure 1 (b), SEM image of the first layer is shown in Figure 1 (c) in .

[0118] In this embodiment, the mullite fiber has a lithium affinity property, which can promote the uniform deposition of lithium ions on the surface of the mullite fiber and enhance the cycle stability of the battery cell.

[0119] The composite diaphragm of this embodiment can delay the occurrence time of thermal runaway and reduce the peak temperature when thermal runaway occurs.

[0120] Example 2

[0121] The present embodiment provides a composite diaphragm, the composite diaphragm is composed of a stacked first layer and a second layer, the first layer is a mullite fiber layer, the mullite fiber layer is a porous layer formed by overlapping mullite fibers, the second layer includes a mixture, the mixture includes a polymer (polyvinylidene fluoride-hexafluoropropylene copolymer, PVDF-HFP) and a composite, the composite includes a one-dimensional carbon material (carbon nanotubes, CNTs) and polydopamine coated on the surface of the one-dimensional carbon material, the mass ratio of the composite to the polymer is 0.007, and the mass ratio of the one-dimensional carbon material to the polydopamine in the composite is 0.01;

[0122] The thickness of the first layer is A, the thickness of the second layer is B, A=2 μm, B=5 μm, and A / (A+B) is 2 / 7.

[0123] This embodiment also provides a method for preparing the above-mentioned composite membrane, comprising the following steps: 1. Preparation of mullite fiber membrane

[0124] First, 1.25g polyacrylamide and 20g silica sol were dispersed in 25mL of pure water and mechanically stirred for 2h until the solution was uniform. Then 10g of short mullite fiber was added to the solution and continued to stir until a uniform slurry was formed. After stirring evenly, the slurry was poured into a homemade mold, left to stand for 1h, the excess solution was filtered out, and then the mold was placed in a 60℃ oven and dried for 10h. After drying, the blank was cut using a punching die, and finally the cut blank was sandwiched between magnesium oxide support plates and placed in a tubular furnace and sintered at 800℃ for 2h to obtain a mullite fiber diaphragm.

[0125] 2. Preparation of CNT@PDA core-shell nanotubes

[0126] Multi-walled carbon nanotubes (CNTs) were added to water and ethanol in a mass ratio of 1:1, and ultrasonically dispersed for 1 hour to obtain a CNTs dispersion. Dopamine hydrochloride (DA) was then added to the CNTs dispersion and magnetically stirred for 5 minutes, and then a methacryloxypropyl trimethoxysilane aqueous solution (Tris aqueous solution) was added and stirred for 12 hours. Among them, the mass ratio of CNTs, DA and Tris was 2:2:1.5, and then centrifuged, washed with deionized water 3 times, and placed in an 80°C oven to dry for 24 hours to obtain CNT@PDA core-shell nanotube powder.

[0127] 3. Preparation of CNT@PDA / mullite composite membrane

[0128] At room temperature, PVDF-HFP powder and CNT@PDA core-shell nanotubes were dissolved in acetone and rapidly magnetically stirred until the particles were completely dispersed and uniformly dispersed, and then placed in a 55°C water bath, stirred for 30 min, and then cooled and stirred at room temperature to obtain a composite solution;

[0129] The coating was carried out using a coating machine at 2 cm s -1 The composite solution was coated on the mullite fiber membrane at a coating speed and dried at room temperature for 1 h to obtain a CNT@PDA / mullite composite membrane, also known as a composite membrane.

[0130] Example 3

[0131] The present embodiment provides a composite diaphragm, the composite diaphragm is composed of a stacked first layer and a second layer, the first layer is a mullite fiber layer, the mullite fiber layer is a porous layer formed by overlapping mullite fibers, the second layer includes a mixture, the mixture includes a polymer (polyvinylidene fluoride-hexafluoropropylene copolymer, PVDF-HFP) and a composite, the composite includes a one-dimensional carbon material (carbon nanotubes, CNTs) and polydopamine coated on the surface of the one-dimensional carbon material, the mass ratio of the composite to the polymer is 0.008, and the mass ratio of the one-dimensional carbon material to the polydopamine in the composite is 0.1;

[0132] The thickness of the first layer is A, the thickness of the second layer is B, A=3 μm, B=4 μm, and A / (A+B) is 3 / 7.

[0133] This embodiment also provides a method for preparing the above-mentioned composite diaphragm, comprising the following steps:

[0134] 1. Preparation of Mullite Fiber Diaphragm

[0135] First, 5g of polyacrylamide and 5g of silica sol were dispersed in 25mL of pure water and mechanically stirred for 2h until the solution was uniform. Then 1g of short mullite fiber was added to the solution and continued to stir until a uniform slurry was formed. After stirring evenly, the slurry was poured into a homemade mold, left to stand for 1h, the excess solution was filtered out, and then the mold was placed in a 60℃ oven and dried for 10h. After drying, the blank was cut using a punching die, and finally the cut blank was sandwiched between magnesium oxide support plates and placed in a tubular furnace and sintered at 1300℃ for 2h.

[0136] 2. Preparation of CNT@PDA core-shell nanotubes

[0137] Multi-walled carbon nanotubes (CNTs) were added to water and ethanol in a mass ratio of 1:1, and ultrasonically dispersed for 1 hour to obtain a CNTs dispersion. Dopamine hydrochloride (DA) was then added to the CNTs dispersion and magnetically stirred for 5 minutes, and then a methacryloxypropyl trimethoxysilane aqueous solution (Tris aqueous solution) was added and stirred for 12 hours. Among them, the mass ratio of CNTs, DA and Tris was 1:1:1.5, and then centrifuged, washed with deionized water 3 times, and placed in an 80°C oven to dry for 24 hours to obtain CNT@PDA core-shell nanotube powder.

[0138] 3. Preparation of CNT@PDA / mullite composite membrane

[0139] At room temperature, PVDF-HFP powder and CNT@PDA core-shell nanotubes were dissolved in acetone and rapidly magnetically stirred until the particles were completely dispersed and uniformly dispersed, and then placed in a 55°C water bath, stirred for 30 min, and then cooled and stirred at room temperature to obtain a composite solution;

[0140] The coating was applied with a speed of 0.5 cm s -1 The composite solution was coated on the mullite fiber membrane at a coating speed and dried at room temperature for 1 h to obtain a CNT@PDA / mullite composite membrane, also known as a composite membrane.

[0141] Example 4

[0142] The present embodiment provides a composite diaphragm, the composite diaphragm is composed of a stacked first layer and a second layer, the first layer is a mullite fiber layer, the mullite fiber layer is a porous layer formed by overlapping mullite fibers, the second layer includes a mixture, the mixture includes a polymer (polyvinylidene fluoride-hexafluoropropylene copolymer, PVDF-HFP) and a composite, the composite includes a one-dimensional carbon material (carbon nanotubes, CNTs) and polydopamine coated on the surface of the one-dimensional carbon material, the mass ratio of the composite to the polymer is 0.067, and the mass ratio of the one-dimensional carbon material to the polydopamine in the composite is 0.05;

[0143] The thickness of the first layer is A, the thickness of the second layer is B, A=4 μm, B=3 μm, and A / (A+B) is 4 / 7.

[0144] This embodiment also provides a method for preparing the above-mentioned composite diaphragm, comprising the following steps:

[0145] 1. Preparation of Mullite Fiber Diaphragm

[0146] First, 5g of polyacrylamide and 20g of silica sol were dispersed in 25mL of pure water and mechanically stirred for 2h until the solution was uniform. Then 20g of short mullite fiber was added to the solution and continued to stir until a uniform slurry was formed. After stirring evenly, the slurry was poured into a homemade mold, left to stand for 1h, the excess solution was filtered out, and then the mold was placed in a 60℃ oven and dried for 10h. After drying, the blank was cut using a punching die, and finally the cut blank was sandwiched between magnesium oxide support plates and placed in a tubular furnace and sintered at 1300℃ for 2h to obtain a mullite fiber diaphragm.

[0147] 2. Preparation of CNT@PDA core-shell nanotubes

[0148] Multi-walled carbon nanotubes (CNTs) were added to water and ethanol in a mass ratio of 1:1, and ultrasonically dispersed for 1 hour to obtain a CNTs dispersion. Dopamine hydrochloride (DA) was then added to the CNTs dispersion and magnetically stirred for 5 minutes, and then a methacryloxypropyl trimethoxysilane aqueous solution (Tris aqueous solution) was added and stirred for 12 hours. Among them, the mass ratio of CNTs, DA and Tris was 1:2:1, and then centrifuged, washed with deionized water 3 times, and placed in an 80°C oven to dry for 24 hours to obtain CNT@PDA core-shell nanotube powder.

[0149] 3. Preparation of CNT@PDA / mullite composite membrane

[0150] At room temperature, PVDF-HFP powder and CNT@PDA core-shell nanotubes were dissolved in acetone and rapidly magnetically stirred until the particles were completely dispersed and uniformly dispersed, and then placed in a 55°C water bath, stirred for 30 min, and then cooled and stirred at room temperature to obtain a composite solution;

[0151] The coating was carried out using a coating machine at 2 cm s -1 The composite solution was coated on the mullite fiber membrane at a coating speed and dried at room temperature for 1 h to obtain a CNT@PDA / mullite composite membrane, also known as a composite membrane.

[0152] Example 5

[0153] The difference between this embodiment and embodiment 1 is that the sum of the thickness A of the first layer and the thickness B of the second layer is the same as that of embodiment 1, and A / (A+B) is 0.5 / 8.

[0154] Example 6

[0155] The difference between this embodiment and embodiment 1 is that the sum of the thickness A of the first layer and the thickness B of the second layer is the same as that of embodiment 1, and A / (A+B) is 5.5 / 8.

[0156] Example 7

[0157] The difference between this embodiment and embodiment 1 is that the mass ratio of the composite to the polymer is 0.003.

[0158] Example 8

[0159] The difference between this embodiment and embodiment 1 is that the mass ratio of the composite to the polymer is 0.15.

[0160] Comparative Example 1

[0161] This comparative example provides a separator, which is different from Example 1 in that the separator does not contain a second layer.

[0162] The difference between the preparation method and Example 1 is that step 2-3 is not performed.

[0163] Comparative Example 2

[0164] This comparative example provides a diaphragm, which is different from Example 1 in that the diaphragm does not contain a mullite fiber diaphragm.

[0165] The preparation method thereof is different from that of Example 1 in that step 1 is not performed.

[0166] Comparative Example 3

[0167] This comparative example provides a PDA membrane, which is different from Example 1 in that the membrane does not contain mullite fibers or carbon nanotubes.

[0168] The preparation method comprises the following steps:

[0169] 1. Preparation of PDA

[0170] Dopamine hydrochloride (DA) was added to water and ethanol in a mass ratio of 1:1, and ultrasonically dispersed for 1 hour. Then, a methacryloxypropyl trimethoxysilane aqueous solution (Tris aqueous solution) was added and stirred for 12 hours. The mass ratio of DA to Tris was 2:1.5, and then centrifuged, washed with deionized water 3 times, and dried in an oven at 80°C for 24 hours to obtain PDA powder.

[0171] 2. Preparation of PDA Membrane

[0172] At room temperature, PVDF-HFP powder and PDA were dissolved in acetone and rapidly magnetically stirred until the particles were completely dispersed and uniformly dispersed, and then placed in a 55°C water bath, stirred for 30 min, and then cooled and stirred at room temperature to obtain a composite solution;

[0173] The coating was carried out using a coating machine at 1 cm s -1 The composite solution was coated on a glass plate at a coating speed of , and dried at room temperature for 1 h to obtain a PDA membrane on the glass plate.

[0174] Battery preparation:

[0175] Preparation of negative electrode sheet: Lithium foil was used as the negative electrode active material and bonded to copper foil. The size of the negative electrode sheet was (100 mm × 55 mm).

[0176] Preparation of positive electrode: using ternary material NCM811 (chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) is used as the positive electrode active material, which is mixed with the conductive agent SP and the binder PVDF in a mass ratio of 97:2:1, coated on an aluminum foil, and made into a positive electrode sheet after drying, pressing and other processes. The size of the positive electrode sheet is 96mm×51mm.

[0177] The separators prepared in the respective Examples and Comparative Examples were used as separators.

[0178] The electrolyte is 1 mol / L LiPF 6 The solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1.

[0179] For the full cell, the capacity ratio of the positive electrode to the negative electrode is 1.2, and the loading of the negative electrode is 9.8 mg cm -2 .

[0180] The assembly process adopts the soft pack lamination method. Specifically, the lamination process is: stack the positive electrode sheet, the diaphragm, and the negative electrode sheet in order to obtain a battery cell. Assembly: The stacked battery cell is hot-pressed and placed in an aluminum-plastic film for top and side sealing. Injection: The electrolyte is injected into the battery, wherein the solvent of the electrolyte is a mixed solvent of EC, EMC and DEC, and the volume ratio satisfies Vol (EC: EMC: DEC) = 2: 1: 2, and the solute is 1 mol / L lithium hexafluorophosphate. Packaging: The battery after injection is sealed, and the injection coefficient is 3g / Ah. Formation: The packaged battery is subjected to formation treatment.

[0181] Test methods and test conditions:

[0182] (1) Porosity test of diaphragm: mercury intrusion method. The results are shown in Table 1.

[0183] (2) Contact angle test of the diaphragm: the equipment used is a contact angle measuring instrument. The electrolyte (with the same composition as the electrolyte used in the above-mentioned battery assembly) is dripped onto the surface of the diaphragm. Note that when the diaphragm contains Fe 3 When the P@PVA composite diaphragm is used, the contact angle of this side surface is measured, and the results are shown in Table 2. The size of the contact angle can reflect the electrolyte affinity of the diaphragm.

[0184] (3) Test of high temperature shrinkage of the diaphragm: The diaphragm was placed at 200°C for 1 hour, and the area shrinkage rate of the diaphragm was calculated using the formula: Area shrinkage rate = (area before shrinkage - area after shrinkage) / area before shrinkage. The results are shown in Table 3.

[0185] (4) The electrochemical performance of the battery was tested. The charge and discharge cut-off voltage was set to 2.8-4.2 V, the charge and discharge current was 1 A / g, and the test was terminated after 2000 cycles. The first efficiency and 2000-cycle capacity retention rate were recorded. The results are shown in Table 4.

[0186] Table 1

[0187] Example Porosity (%) Example 1 45.6 Example 2 44.2 Example 3 41.7 Example 4 44.8 Example 5 44.2 Example 6 43.7 Example 7 44.1 Example 8 43.2 Comparative Example 1 31.1 Comparative Example 2 34.6 Comparative Example 3 36.9

[0188] Table 1 shows that the porosity of the composite diaphragm of the present invention is very high, which is above 41.7%, which can ensure that Li + Pass quickly.

[0189] Table 2

[0190] Example Contact angle (°) Example 1 6.9 Example 2 10.0 Example 3 8.9 Example 4 11.2 Example 5 7.9 Example 6 8.1 Example 7 8.6 Example 8 9.1 Comparative Example 1 19.4 Comparative Example 2 11.4 Comparative Example 3 4.1

[0191] It can be seen from Table 2 that the introduction of the mullite layer can fully reduce the contact angle of the diaphragm to below 11.2°, thereby accelerating the electrolyte infiltration.

[0192] Table 3

[0193]

[0194]

[0195] It can be seen from Table 3 that the area shrinkage of the composite diaphragm of the present invention at 200° C. is less than 11.2%, which can improve the heat resistance of the diaphragm.

[0196] Table 4

[0197]

[0198]

[0199] The SEM image of the negative electrode surface of the battery made of the composite separator of Comparative Example 1 after 500 cycles is shown in Figure 2 (a) of the figure shows the SEM image of the negative electrode surface of the battery made of the separator of Example 1 after 500 cycles. Figure 2 By comparison, it can be seen that the surface of the composite membrane of the present invention is smoother, indicating that the present invention can effectively promote Li + Uniform deposition and inhibition of lithium dendrite deposition.

[0200] It can be seen from Table 4 that the battery assembled using the composite diaphragm of the present invention has a higher first efficiency and excellent cycle performance.

[0201] At the same time, through the comparison between Example 1 and Examples 5-6, it can be seen that a thickness ratio of the mullite fiber layer that is too high or too low is not conducive to the first effect of the battery cell and the capacity retention rate during a long cycle.

[0202] By comparing Example 1 with Examples 7-8, it can be seen that the content of the polymer plays a key role in the cycle stability of the battery cell.

[0203] By comparing Example 1 with Comparative Example 1, it can be seen that the second layer material has an important influence on the cycle stability of the battery cell.

[0204] By comparing Example 1 with Comparative Example 2, it can be seen that the absence of mullite fibers in the diaphragm will reduce the first effect and cycle stability, especially the cycle stability will be greatly reduced.

[0205] By comparing Comparative Example 2 with Comparative Example 3, it can be seen that carbon nanotubes have an impact on the long cycle performance of the battery cell.

[0206] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite diaphragm, characterized in that: The composite membrane comprises a first layer and a second layer, wherein the first layer is a mullite fiber layer, and the second layer comprises a mixture, wherein the mixture comprises a polymer and a composite, and the composite comprises a one-dimensional carbon material and polydopamine coated on the surface of the one-dimensional carbon material.

2. The composite diaphragm according to claim 1, characterized in that: The thickness of the first layer is A, the thickness of the second layer is B, and A and B satisfy the relationship: 1 / 8≤A / (A+B)≤5 / 8.

3. The composite diaphragm according to claim 1 or 2, characterized in that: The mullite fiber layer is a porous layer formed by overlapping mullite fibers; Preferably, the polymer is a fluorine-containing polymer, preferably including at least one of polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether, polyvinylidene fluoride, fluorinated polyimide, fluororubber, fluorovinyl ether copolymer, perfluoropolyether, perfluoroethylene propylene copolymer and fluorinated polyarylether nitrile; Preferably, in the composite, the one-dimensional carbon material comprises at least one of carbon nanotubes and carbon fibers; Preferably, in the composite, the mass ratio of the one-dimensional carbon material to the polydopamine is 0.01-0.1; Preferably, the mass ratio of the composite to the polymer is 0.005-0.

1.

4. The composite diaphragm according to any one of claims 1 to 3, characterized in that: The first layer and the second layer are both located at the outermost sides of the composite diaphragm.

5. A method for preparing a composite diaphragm according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) preparing a mullite fiber layer; (2) dispersing the one-dimensional carbon material, dopamine hydrochloride and a stabilizer in a first solvent and reacting them to obtain a composite; (3) dissolving the polymer and the composite in a second solvent and stirring them uniformly to obtain a composite solution; (4) coating the composite solution on the mullite fiber layer prepared in step (1), and drying the composite membrane.

6. The preparation method according to claim 5, characterized in that: Step (1) comprises: providing a dispersion medium, adding mullite fibers into the dispersion medium to form a dispersion system, drying the dispersion system and then subjecting it to high-temperature molding to obtain the mullite fiber layer.

7. The preparation method according to claim 6, characterized in that: After adding mullite fiber to the dispersion medium, heating and stirring are performed to form the dispersion system, and the heating temperature is 80° C.-120° C.; Preferably, the viscosity of the dispersed system is μ2,50cP≤μ2≤30000cP; Preferably, the dispersion system is allowed to stand and filtered before the drying step is performed; Preferably, the sintering temperature of the high temperature forming is 800°C-1800°C; Preferably, the sintering time of the high temperature molding is 0.5h-10h; Preferably, in the high temperature forming step, the dried precursor is sandwiched between sintering plates for sintering.

8. The preparation method according to claim 6 or 7, characterized in that: The dispersion medium is a glue solution, which is obtained by mixing a binder and water and heating them; Preferably, the temperature at which the binder and the water are mixed and heated is 80°C-120°C; Preferably, the viscosity of the glue solution is μ1,50cP≤μ1≤20000cP; Preferably, the binder comprises at least one of polyacrylamide, silica sol and polyvinylidene fluoride-hexafluoropropylene copolymer; Preferably, the mass ratio of the mullite fiber to the binder is 10-100.

9. The preparation method according to any one of claims 5 to 8, characterized in that: Step (2) the first solvent is an aqueous solvent; Preferably, the aqueous solvent comprises ethanol and water; Preferably, the stabilizer comprises at least one of 3-(methacryloxypropyl)tris(trimethylsiloxy)silane aqueous solution, anhydrous ethanol and nitrogen methyl pyrrolidone; Preferably, step (2) comprises: (a) dispersing the one-dimensional carbon material in the first solvent to obtain a first solution; (b) adding the dopamine hydrochloride and the stabilizer to the first solution, heating and stirring to obtain a composite.

10. A secondary battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The separator is a composite separator according to any one of claims 1 to 4 or a composite separator prepared by the method according to any one of claims 5 to 9, wherein the first layer of the composite separator is arranged close to the negative electrode, and the second layer is arranged close to the positive electrode; Preferably, the negative electrode is a lithium metal negative electrode.

Citation Information

Patent Citations

  • Aluminum silicate ceramic fiber diaphragm of lithium-air battery and preparation method thereof and lithium-air battery

    CN112018308A

  • Porous ceramic fiber diaphragm material for thermal battery and preparation method of porous ceramic fiber diaphragm material

    CN113644379A

  • Composite diaphragm modified by core-shell nanotube type structure material as well as preparation method and application of composite diaphragm

    CN115051107A

  • Double-layer composite diaphragm, preparation method thereof and battery

    CN118867574A